2017
DOI: 10.1002/gj.2968
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircon geochronology of the Jurassic strata in the western Ordos Basin, North China: Constraints on the provenance and its tectonic implication

Abstract: U–Pb detrital zircon data from the Jurassic strata in the western Ordos Basin (WOB) show significant age differences between formations, from lower to upper including the Yan'an, Zhiluo, Anding, and Fenfanghe formations. The main peaks in the detrital zircon age spectra of the Yan'an Formation are at ca. 245, 444, 1813, and 2,387 Ma, which resemble those of the underlying Triassic strata in the WOB. Combined with the occurrence of reworked sporopollen and carbonate debris, the sediments of the Yan'an Formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 70 publications
(153 reference statements)
0
4
0
Order By: Relevance
“…There is a continuous negative seismic phase boundary with a length of ~250 km at a depth of 10 km between the Maxianshan fault and the Xiaoguanshan fault, which may be deep evidence of the local overall uplift of the Longzhong block and its extension to the Ordos block. Because the surface along the southeast of the Maxianshan Fault in the study area is covered by thick and near-horizontal sedimentary layers and the faults are not developed, the research level of this area is relatively low, but the Cenozoic strata have obvious structural characteristics of overall uplift (Guo et al, 2018a), so our CCP imaging results have a good correspondence with the geological phenomenon of regional uplift.…”
Section: Crustal Structurementioning
confidence: 95%
See 1 more Smart Citation
“…There is a continuous negative seismic phase boundary with a length of ~250 km at a depth of 10 km between the Maxianshan fault and the Xiaoguanshan fault, which may be deep evidence of the local overall uplift of the Longzhong block and its extension to the Ordos block. Because the surface along the southeast of the Maxianshan Fault in the study area is covered by thick and near-horizontal sedimentary layers and the faults are not developed, the research level of this area is relatively low, but the Cenozoic strata have obvious structural characteristics of overall uplift (Guo et al, 2018a), so our CCP imaging results have a good correspondence with the geological phenomenon of regional uplift.…”
Section: Crustal Structurementioning
confidence: 95%
“…FIGURE 8A Map showing the Middle Jurassic-Early Cretaceous unconformity relationships of the southwestern margin of the Ordos block (adapted fromTang et al, 1992;Guo et al, 2018a;Peng et al, 2022b). The location of the study area is shown in Figure1B.…”
mentioning
confidence: 99%
“…In the western SOB, the East Piedmont Liupanshan and East Piedmont Kongtongshan faults separate the NQLB, Hexi corridor transition belt, and the western Ordos Basin margin from east to west (Figure 1; Guo et al., 2018). From north to south, the Qilian Orogenic Belt can be divided into three nearly parallel secondary tectonic units: the NQLB, Central Qilian Block and South Qilian Belt.…”
Section: Geologic Settingmentioning
confidence: 99%
“…U-Pb dating of detrital zircons informs provenance analysis and regional tectonic evolution (Gehrels et al 1995;Zhao et al 2015;Guo et al 2018). Therefore, the focus of this work is to compare the provenance on the east and west sides of the Middle Permian Lower Shihezi Formation in the northern Ordos Basin through systematic petrological and quantitative mineralogical analysis.…”
Section: Introductionmentioning
confidence: 99%